EFFECTIVENESS OF FLIPPED CLASSROOM MODEL THROUGH MULTIMEDIA TECHNOLOGY IN IMPROVING STUDENTS' PERFORMANCE IN DIRECTED NUMBERS - Haji Muhamad Hafizuddin Haji Mohamad Ali; Daniel Asamoah; Masitah Shahrill (IKIP Siliwangi and I-MES, 2022)
The recent globalisation and the emergency of COVID-19 require a teaching and learning environment that encourages the use of technology. Through a mixed-method design and an action research approach, this study investigated the effectiveness of a flipped classroom model through multimedia technology in improving students’ performance in directed numbers, given the difficulty and misconceptions of students in this mathematical concept. A total of 30 Year 9 students conveniently sampled from one of the secondary schools in Brunei Darussalam served as participants. The action taken involved a pretest, intervention, posttest, and interviews. The results of the paired sample t-test revealed that students’ performance in directed numbers significantly improved after the flipped classroom intervention. Students had positive perceptions of the flipped classroom model as it encouraged their readiness, participation, and motivation. Challenges such as time constraints and distractions when studying from home were reported. These results imply that amid COVID-19, a flipped classroom through multimedia technology can be an effective and alternative way of teaching and learning directed numbers. It has the potential of encouraging student-centred learning and creativity, which are vital in teaching and learning mathematics.